The Social System of the Family in the Islamic Educational Perspective: Comparative Study - Al-Jarrah, Farouq Abdel Kareem (Journal of Humanities & Social Sciences, 2021)
The study aimed to reveal the social system of the family, In the Islamic educational perspective, and the researcher used the analytical inductive approach, in his study of texts and opinions, and the deductive approach to extract the concepts and principles of the family’s social system, and it consisted of the following investigations: The first topic: the family, its concept and its position, and the second topic addressed: principles The social system of the family related to the marital relationship is a comparative study with the structural functional, and as for the third topic: the principles of the social system of the family in the relationship of fathers with children, the study reached several results, the most important of which are: that the family idiomatically: the social entity consisting of a man and a woman linked by the marital bond, according to The law of God Almighty, and what results from this bond of children, is governed by the approach of Islam, and that the principle of marriage in the relationship is based on the difference of sex, a man and a woman are bound by a legal contract, and in accordance with the human instinct that God Almighty created, and one of the most important recommendations of the study: Explain what is involved He must bear international conventions and conferences about the dangers of violating the Islamic curriculum, with regard to the family, through specialized research studies.